Land use arrangements and environmental damages. A reassessment of the property owners liability - Ruiz, Haraví Eloisa (2016)
Fil: Ruiz, Haraví Eloisa. Universidad Nacional del Nordeste. Facultad de Derecho y Ciencias Sociales y Políticas; Argentina.